Problematika Lembaga Pendidikan Islam di Era Disrupsi Digital: (Tantangan dan Strategi Adaptasi) - Yogi Arrohman; Khairil Hidayat; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The era of digital disruption has brought significant changes to various aspects of life, including Islamic education. Islamic educational institutions face various challenges, such as limited digital literacy among educators, minimal use of technology in the learning process, disparities in access to digital infrastructure, and challenges in maintaining Islamic values ​​amidst the flow of information globalization. Furthermore, the changing character of students, who are increasingly familiar with technology, demands innovation in learning methods and media. This study aims to identify the various challenges facing Islamic educational institutions in the era of digital disruption and formulate relevant adaptation strategies. The method used is a literature review analyzing various related scientific sources. The results of the study indicate that possible adaptation strategies include improving educators' digital competencies, integrating technology into the curriculum, strengthening character based on Islamic values, and developing flexible and innovative digital-based learning systems. Thus, Islamic educational institutions are expected to survive and develop adaptively without losing their identity and core values.